Casein hydrolysate supplementation in low‐crude protein diets increases feed intake and nitrogen retention without affecting nitrogen utilization of growing pigs. (8th January 2020) - Shen, Junhua; Wang, Huisong; Pi, Yu; Gao, Kan; Zhu, Weiyun
Abstract: BACKGROUND: An extreme reduction of the crude protein (CP) level in diets, even balanced with amino acids (AAs), is detrimental for intestinal nitrogen (N) metabolism and the growth of pigs. This study investigated the effects of casein hydrolysate supplementation in low‐CP diets on growth performance, N balance, and intestinal N supply for pigs. A total of 24 barrows were randomly assigned to one of three dietary treatments of 160 g kg −1 CP (control), 130 g kg −1 CP (LAA), and 130 g kg −1 CP plus casein hydrolysate (LCH) for 28 days. RESULTS: The LCH group had a higher average daily feed intake (ADFI) and average daily gain (ADG) than the LAA group, and a higher ADG than the control ( P  < 0.05). Compared with the control, both the LAA and LCH decreased N intake, serum urea N, fecal N, and N excretion, and increased apparent N availability, with LCH having higher N intake and N retention than LAA group ( P  < 0.05). Compared with LAA, LCH increased ileal fluxes of CP and AA ( P  < 0.05), and with values similar to those of the control. However, ileal flows of CP and AA were similar between LCH and LAA, both of which were lower than those in the control ( P  < 0.05). CONCLUSION: Using protein hydrolysate to replace some crystalline AAs in low‐CP diets increased feed intake, N retention and ADG without affecting N utilization. These findings point to the important impact of protein hydrolysate supplementation on improving growth for pigs fed low‐CP diets. © 2019 Society of Chemical Industry